Pengaruh Pelatihan Bantuan Hidup Dasar Terhadap Pengetahuan Pemuda Karang Taruna Di Kelurahan Baros Wilayah Kerja Puskesmas Baros Kota Sukabumi - Ady; Dedi (Politeknik Kesehatan TNI AU Ciumbuleuit Bandung, 2024)
ABSTRACT Cardiac arrest often occurs suddenly, where a person who initially appears healthy can abruptly lose consciousness due to a heart attack. This condition signifies a sudden cessation of the heart's pumping function, leading to a halt in blood circulation throughout the body and potentially causing permanent brain damage. It is usually caused by heart conditions such as heart failure or coronary artery disease. The aim of this research is to identify the impact of Basic Life Support (BLS) training on knowledge of BLS among members of youth organizations (Karang Taruna). Data collection was performed using a cross-sectional approach. The research results indicate that there are differences in the average knowledge, attitudes, and skills before and after BLS training within the intervention group, as well as differences in the average knowledge, attitudes, and skills before and after BLS training between the intervention and control groups. Keywords : Cardiac arrest, Basic Life Support (BLS), Knowledge